Platelet-rich plasma is similar to platelet-rich plasma plus hyaluronic acid for the treatment of knee osteoarthritis at 2 years: a randomized controlled trial - Eric A. Branch; Joshua J. Cook; Achraf Cohen; Hillary Plummer; Alireza Emami; Jessica Truett; Adam W. Anz (Elsevier, 2023)
Introduction: Autologous platelet-rich plasma (PRP) and hyaluronic acid (HA) are common treatments for knee osteoarthritis (OA). Several studies have demonstrated PRP as a safe and effective treatment for OA and, in some studies, produces a better outcome than HA. Objective: The primary objective of this study was to determine if HA injected with PRP would improve the efficacy of treatment of symptomatic knee OA compared to PRP alone. We hypothesized that the addition of HA would improve the efficacy of (PRP). Methods: A total of 64 participants with Kellgren-Lawrence (KL) Grades 1 to 4 knee OA were randomized into 2 groups and scheduled to receive 3-injections. Group 1 [PRP] received injections of PRP. Group 2 [HA+PRP] received the same treatment, with an additional HA injection for the first 2 injections. Both groups were blindfolded for the first 2 injections. To evaluate the efficacy of the regimen, participants completed patient reported outcome measures (PROMs). PROMs were completed prior to injections and at 1, 3, 6, 12, 18, and 24 months after the final injection. Results: Participants in both groups felt pain consistent with standard-of-care HA injection regimens with no difference in perceived pain. No infections or complications were observed. All PROM scores demonstrated improvement over baseline from 1-24 months post injections. There were no statistically significant differences between the groups. Conclusions: For the treatment of OA, PRP alone or PRP concomitantly with HA performed similarly out to 24 months. PRP in combination with HA was not superior to PRP alone.